Research on anchor service life base on grey prediction model - Xinzheng Wang (Fracture and Structural Integrity)
With the wide application of anchored structures in various engineering, their durability and service life have become an important issue in the development of anchoring technique. According to the corrosion experiment results on different working conditions (close and damp, permanently soaked in water, wet and dry alternately, weak acidity aqueous soaking), and on the basis of determining the loss rate threshold of anchor steel reinforcement bearing capacity, this paper first test the experiment data and then predict the service life of anchor steel on four different working conditions by adopting GM (1,1) model. The results indicate that the grey prediction has a high accuracy.